Madame Bovary - Flaubert, Gustave (London: HarperPress, 2011)
HarperCollins is proud to present its new range of best-loved, essential classics. ''for her, life was as cold as an attic with a window looking to the north, and ennui, like a spider, was silently spinning its shadowy web in every cranny of her heart.' Married to Charles, a provincial doctor, Emma Bovary yearns for a more glamorous life. Disenchanted with her husband and seeking an escape from their dull marriage she is soon tempted into a brief romantic liaison with another man. Although short-lived, she remains desirous of passion and the finer things in life and embarks on another affair, destroying her reputation. Considered scandalous at the time, Emma Bovary's superficial and immoral behaviour shocked readers and caused moral outcry. Flaubert holds up to ridicule not only Madame Bovary herself, but the society that dares to judge her
Keywords: Fiction